2020
DOI: 10.1136/bmjopen-2020-036923
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for the impact of gardens and gardening on health and well-being: a scoping review and evidence-based logic model to guide healthcare strategy decision making on the use of gardening approaches as a social prescription

Abstract: ObjectiveTo systematically identify and describe studies that have evaluated the impact of gardens and gardening on health and well-being. A secondary objective was to use this evidence to build evidence-based logic models to guide health strategy decision making about gardens and gardening as a non-medical, social prescription.DesignScoping review of the impact of gardens and gardening on health and well-being. Gardens include private spaces and those open to the public or part of hospitals, care homes, hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 91 publications
(62 reference statements)
3
67
1
5
Order By: Relevance
“…Previous studies highlighted the beneficial contribution of gardens to Alzheimer’s disease patients [ 17 19 ]. Whear et al [ 20 ] published a systematic review in 2014 to assess the effects of gardens on the health of nursing home residents with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies highlighted the beneficial contribution of gardens to Alzheimer’s disease patients [ 17 19 ]. Whear et al [ 20 ] published a systematic review in 2014 to assess the effects of gardens on the health of nursing home residents with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The gardens in these studies were not specially designed for nursing home residents, except in the study by Edwards [ 21 ] in which the garden that was specially designed for nursing home residents with dementia. In their scoping review, Howarth [ 17 ] et al identified 14 studies which assessed the effects of gardening on patients with dementia and they concluded that it contributes to positive behaviour changes and better quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to remember that having a domestic garden is also strongly associated with socioeconomic status [ 45 ]. Still, the perceived restrictiveness of private gardens has been reported to rank higher than that of other private spaces [ 46 ], and gardening has been associated with reduced anxiety, depression, and many other mental health benefits [ 42 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to remember that having a domestic garden is also strongly associated with socioeconomic status (46). Still, the perceived restrictiveness of private gardens has been reported to rank higher than of other private spaces (47) and gardening has been associated with reduced anxiety, depression, and many other mental health benefits (43,48).…”
Section: Introductionmentioning
confidence: 99%